EFEKTIVITAS BIOFERTILIZER EXTRAGEN DAN PUPUK NPK YARAMILA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KUBIS BUNGA (Brassica oleracea var. botrytis L.) - Widyana Rahmatika; Indra Bagus Sasmito (Universitas Islam Kadiri, 2017)
The purpose of this study to determine the effect of liquid organic fertilizer Biofertilizer Extragen and NPK Yaramila on the growth and production of cauliflower (Brassica oleracea var. botritis L.) varieties PM 126 F1.The experiment was conducted on Januari until April 2014 in the land of experimentation Sobontoro vilage, Boyolangu subdistric, Tulungagung regency. The experiment design use Randomized Block Design with two factor repeated three times. The first factor is Biofertilizer Extragen liquid organic fertilizer consist of three level : 400 liter/hectare, 800 liter/hectare, 1.200 liter/hectare. The second factor is doses of fertilizer NPK Yaramila consist of three levels : 1 Ton /Ha, 1,4 Ton /Ha, 1,8 Ton /Ha. The results showed that the combined treatment of fertilizer Biofertilizer extragen and fertilizer NPK yaramila (E3Y3) can show the interaction was highly significant on plant height age of 35 years days after plant (53,73 cm), and this is indicated in the treatment of fertilizer Biofertilizer extragen and fertilizer NPK yaramila (E3Y3) interaction was highly significant on the number of leaf ages 35 days after plant (14,75 cm). In destructive observation parameters highly significant interaction showed the combination treatment dose (E3Y3) the wet weight of flowers(718,333 gr) and generate heavy interest 3 Ton/Ha, but no interaction on the parameters of the mass diameter and length of flower plants